The Overdense Environments of WISE-Selected, Ultra-Luminous, High-Redshift AGN in the Submillimeter - Jones, Suzy F. (Frontiers in Astronomy and Space Sciences, 2017)
The environments around WISE-selected hot dust obscured galaxies (Hot DOGs) and WISE/radio-selected active galactic nuclei (AGNs) at average redshifts of z = 2.7 and z = 1.7, respectively, were found to have overdensities of companion Submillimeter-selected sources. The overdensities were of ~2–3 and ~5–6, respectively, compared with blank field submm surveys. The space densities in both samples were found to be overdense compared to normal star-forming galaxies and Submillimeter galaxies (SMGs). All of the companion sources have consistent mid-IR colors and mid-IR to submm ratios to SMGs. Monte Carlo simulations show no angular correlation, which could indicate protoclusters on scales larger than the SCUBA-2 1.5 arcmin scale maps. WISE-selected AGNs appear to be good indicators of overdense areas of active galaxies at high redshift.